Diffuse large B-cell lymphoma, NOS. Clinicopathological study in a cohort of peruvian patients - Dueñas Hancco, Daniela (2020)
Objective. To evaluate the clinicopathological characteristics of diffuse large B-cell lymphoma, not otherwise specified (LCBGD, NOS), in a cohort of peruvian patients. Methods. Seventy-two cases with a diagnosis of LCBGD, NOS, were studied at the INEN. Clinicopathological characteristics, overall survival (OS) and other clinical parameters were evaluated according to origin cell, Epstein-Barr virus infection (EBER), and the immunohistochemical expression (IHC) of MYC and BCL2. Results. There were 54% women and 46% men, with an average age of 65 years. 76% were ganglionic, the majority cervical location and 24% extranodal, the stomach being the most affected. The most frequent stages were II (35%) and III (29%), the majority with medium-high and high IPI. Histologically, almost all cases had centroblastic and immunoblastic morphology. There was a similar proportion of cases with germinal center (GCB) and non-germinal center (non-GCB) subtypes. GCB and EBER+ had better OS than non-GCB and EBER-, respectively. Likewise, cases with negative IHC for MYC and BCL2 had better OS and a higher percentage in early stages. These findings were not statistically significant. Conclusion.Our cases show characteristics similar to those described in the literature, although with a higher percentage associated with EBV and non-GCB cases. The small number of cases evaluated with IHC to determine subtypes and biomarkers may have limited the statistical analysis in this cohort of cases.